Determination of meloxicam in human plasma by ultra‐high‐performance liquid chromatography–tandem mass spectrometry and its application in a pharmacokinetic study. (29th May 2022) - Zhang, Siyao; Chen, Shutong; Song, Yujing; Xin, Ying; Cui, Ying; Qin, Feng
Abstract: A rapid, selective and sensitive ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method was developed to detect meloxicam in human plasma. A triple quadrupole tandem mass spectrometer equipped with an electrospray ionization source was used in positive ion mode. Protein precipitation with acetonitrile was used for sample preparation. Meloxicam and 13 C6 ‐meloxicam internal standard were analyzed on an Acquity CSH C18 column with a mobile phase of acetonitrile and water in 0.1% formic acid using a gradient program for separation. The retention time of meloxicam was 1.1 min and the total run time was only 2.0 min. Detection was performed in multiple reaction monitoring mode using an electrospray ionization source with optimized mass spectrometry parameters. The calibration curves were linear in the range 10.0–3.00 × 10 3 ng/ml ( r ≥ 0.99). The within‐run and between‐run RSDs were ≤14.8%. The within‐run and between‐run REs ranged from −4.6 to 10.7%. There was no significant matrix effect, and the recovery rate was high. This method was fully validated, including reinjection reproducibility in human plasma. The method was applied to the pharmacokinetic study. All of the incurred sample reanalysis methods met the criteria.